The Dynamic of PRAMEY Isoforms in Testis and Epididymis Suggests Their Involvement in Spermatozoa Maturation - Kern, Chandlar H.; Feitosa, Weber B.; Liu, Wan-Sheng (Frontiers in Genetics, 2022)
The preferentially expressed antigen in melanoma, Y-linked (PRAMEY) is a cancer/testis antigen expressed predominantly in bovine spermatogenic cells, playing an important role in germ cell formation. To better understand PRAMEY’s function during spermatogenesis, we studied the dynamics of PRAMEY isoforms by Western blotting (WB) with PRAMEY-specific antibodies. The PRAMEY protein was assessed in the bovine testicular and epididymal spermatozoa, fluid and tissues, as well as in ejaculated semen. The protein was further examined, at a subcellular level in sperm head and tail, as well as in the subcellular components, including the cytosol, nucleus, membrane, and mitochondria. RNA expression of PRAMEY was also evaluated in testis and epididymal tissues. Our WB results confirmed the previously reported four isoforms of PRAMEY (58, 30, 26, and 13 kDa) in the bovine testis and spermatozoa. We found that testicular spermatozoa expressed the 58 and 30 kDa isoforms. As spermatozoa migrated to the epididymis, they expressed two additional isoforms, 26 and 13 kDa. Similarly, the 58 and 30 kDa isoforms were detected only in the testis fluid, while all four isoforms were detected in fluid from the cauda epididymis. Tissue evaluation indicated a significantly higher expression of the 58 and 13 kDa isoforms in the cauda tissue when compared to both the testis and caput tissue (P<0.05). These results indicated that testis samples (spermatozoa, fluid, and tissue) expressed predominantly the 58 kDa and 30 kDa PRAMEY isoforms, suggesting their involvement in spermatogenesis. In contrast, the 26 kDa isoform was specific to epididymal sperm and the 13 kDa isoform was marked in samples derived from the cauda epididymis, suggesting their involvement in sperm maturation. Results from the sperm head and tail experiments indicated that the 13 kDa isoform increased 4-fold in sperm tails from caput to cauda, suggesting this isoform may have a significant role in tail function. Additionally, the 13 kDa isoform increased significantly (P<0.05) in the cytosol during epididymal passage and tended to increase in other subcellular components. The expression of PRAMEY in the sperm subcellular components during epididymal maturation suggests the involvement of PRAMEY, especially the 13 kDa isoform, in sperm motility.